PEMANFAATAN ALAT RIAS SEBAGAI PENUNJANG DEMONSTRASI PRAKTEK MATA KULIAH PENGETAHUAN PERALATAN RIAS - Warsihapsari, Tri; Yuwati, Herina (Akademi Kesejahteraan Sosial AKK Yogyakarta, 2024)
This research aims to: 1). Find out how far the knowledge of makeup students is about makeup equipment; 2). Know how far students know about the benefits of makeup equipment; and 3). To find out how far the student's knowledge is about the application of makeup equipment. The research methods used are descriptive, quantitative, and qualitative. The subjects in this study are 32 students of the Cosmetology study program in the first semester and 34 students of the 3rd semester of AKS-AKK Yogyakarta. Data collection uses demonstrations, interviews, and observations. The interview and communication method is intended to obtain detailed data on the use of makeup equipment as a support for the demonstration of practical makeup equipment knowledge courses. The demonstration was used to describe the results of the demonstration practice of using makeup equipment so that students better understood and paid attention when using the tools. In this study, there were 36 children who stated that they understood from learning about makeup equipment and 14 others did not understand the use of makeup equipment.